Non-repudiation and privacy-preserving sharing of electronic health records. Issue 1 (31st December 2022) - Sharaf, Mohamed
Abstract: In this work, we present a framework that facilitates the sharing of EHRs among the community of health-care providers (HCPs). However, the sharing might be obstructed by patients' privacy and the controlling legislation. Nevertheless, our sharing scheme of EHRs strives to respect patients' privacy and comply with relevant legislator guidelines, e.g., HIPPA. The proposed work introduces two services while sharing the EHRs: privacy and non-repudiation. To this end, we introduce the partners and the role of each during the course of exchanging of EHRs. The principle of sharing EHRs among HCPs has to be reinforced to save patients' lives while cryptographic primitives have to be employed to serve this purpose. In this paper, we are motivated to introduce the notion of non-repudiation private membership test (NR-PMT). In NR-PMT, we help patients receive medical services with great flexibility while maintaining their privacy and thwarting all possible threats to disclose their identities. In addition, a formal security analysis based on Kailar's accountability framework has been used to analyze the proposed framework. Also, a complexity analysis has been conducted.